Can you hear me? Effects of hearing impairments on verbal and non-verbal communication during collaborative musical performance. (November 2014) - Fulford, Robert; Ginsborg, Jane
This article reports an observational study exploring the effects of naturally-occurring hearing impairments on musicians' behaviour and communication with each other while rehearsing and performing. Two groups of three pianists and three flautists, one in each group with normal hearing, and the others moderately or profoundly deaf, formed duos working on two pieces of music: a movement from a Bach flute sonata and a new composition. The profoundly deaf musicians spent significantly more time looking at and talking to their co-performers than moderately deaf and hearing players. In response, hearing players looked at and talked more to their profoundly deaf partners. Profoundly deaf players also spent significantly less time on complete runs of the pieces from start to finish, without stops. While these findings have implications for the teaching and practice of musicians with and without hearing impairments, we suggest that social factors are as, if not more, important to the success of collaborative musical performance.